First report of the poplar leaf miner, Phyllonorycter populifoliella (Treitschke) (Lepidoptera: Gracillariidae) from India - Shashank, Pathour R.; Singh, Narendra; Harshana, Anand; Sinha, Twinkle; Kirichenko, Natalia (Zootaxa, 2021)
Here we report about the discovery of the poplar leaf miner, Phyllonorycter populifoliella (Treitschke) in India. The mines of this micromoth were found in noticeable density on the leaves of poplar, Populus sp. (Salicaceae) in the northern mountainous region Ladakh in 2017–2018. We provide short morphological diagnosis, describe bionomics and analyze molecular data of Ph. populifoliella from India comparing sequences with those from other countries in Eurasia where the species is known as native. We also illustrate male and female genitalia, an adult of the moth, the leaf mines and the infestation plot in Ladakh, and discuss the occurrence of the species in the country.